Carrier dynamic and carrier Temperature in Quantum Well - Hiba J. Musa; Ahmed H. Flayyih (University of Thi-Qar Journal of Science, 2022)
Carrier temperature in quantum well (QW)semiconductor optical amplifier (SOA) has been studied,depending density matrix theory (DMT) and carrier dynamicin quantum well. The effect of volume carrier density, dopingon effect, pulse shape, nonradiative relaxation, and nonlineargain coefficients on the carrier temperature and carrierheating has been investigated. The theoretical results showthat; the time recovery increases straightforward withnonradiative recombination, where the relaxation time ofnonradiative recombination reduces the rate of carrieroccupation in quantum states. Also, the carrier temperatureincreases with carrier density, free carrier absorption, carrierheating lifetime and reduces with pulse shape of pump pulses